In vitro activity of the alkaloids mixture of Ervatamia coronaria (Jacq) Staff. Apocynaceae on Leishmania braziliensis amastigotes (2008)
Leishmaniasis, caused by Leishmania sp., is one of the mean reason of considerable mortality and morbidity throughout the world, especially in the tropics. Cutaneous and mucocutaneous manifestations are caused by Leishmania braziliensis, and the cutaneous form is the most common one in Colombia. In the search for antileishmanial compounds from natural sources, we studied the alkaloids mixture from Ervatamia coronaria against L. braziliensis at six different concentrations (1.0, 10, 20, 25, 50 and 100 ?g/mL). Macrophages J774 infected with L. braziliensis were treated with alkaloids one hour, and once a day for three days, after parasitic infection and preserving the same culture medium. Cytotoxicity with trypan blue was undertaken in macrophages J774 by using the same concentrations. Three different cultures samples were carried out. As a control we used medium alone. The alkaloids mix showed a dose/dependent activity on amastigote, but by increasing concentrations from 50 to 100 ?g/mL for three days, we saw a high index of infection, probably caused by cellular death. We did not see any toxic effect on macrophages J774 at 100 ?g/mL, LD50/24h= 233.52 ?g/mL. These results revealed a novel pharmacological activity of alkaloids from E. coronaria against amastigotes of L. braziliensis IC50 = 2.6 and 12.4 ?g/mL without toxicity on host cells.